Modeling, Evaluating and Scaling up a Commercial Multilayer Claus Converter Based on Bench Scale Experiments - Sepehr Sadighi; Seyed Reza Seif Mohaddecy; Mehdi Rashidzadeh (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2020)
Industrial scale reactors work adiabatically and measuring their performance in an isothermal bench scale reactor is faced with uncertainties. In this research, based on kinetic models previously developed for alumina and titania commercial Claus catalysts, a multilayer bench scale model is constructed, and it is applied to simulate the behavior of an industrial scale Claus converter. It is shown that performing the bench scale isothermal experiments at the temperature of 307 ºC can reliably exhibit the activity of catalytic layers of an industrial Claus converter operating at the weighted average bed temperature (WABT) of 289 ºC. Additionally, an adiabatic model is developed for a target industrial scale Claus reactor, and it is confirmed that this model can accurately predict the temperature, and molar percentages of H2S and CS2. Based on simulation results, 20% of excess amount of Claus catalysts should be loaded to compensate their deactivation during the process cycle life. Copyright © 2020 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).